ANALISIS KESUKSESAN SIAP BOS (SISTEM INFORMASI APLIKASI PENGELOLAAN BANTUAN OPERASIONAL SEKOLAH) DI KABUPATEN BLORA - Annisa Fatmawati; Budhi Adhiani Christina; Eka Murtiasri (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
The SIAP BOS (Sistem Informasi Aplikasi Pengelolaan Bantuan Operasional Sekolah) application is an online-based application containing budgeting, administration, accountability, and reporting of BOS funds developed by the Blora District Education Office with a third party (PT. Solusi Teknologi Informasi/ Solusiti). This study aims to determine the success of the SIAP BOS application using the DeLone and McLean information system success model. The variables used are system quality, information quality, service quality, user satisfaction, and net benefits. The population of this study is the SIAP BOS application users including principals, BOS treasurers, BOS operators of State Junior High School (SMP in Blora Regency and the BOS Team of the Blora Regency Education Office with a sample of 120 people. Collecting data through the distribution of online questionnaires with a google form. Data of 120 respondents were collected then analyzed by Partial Least Square (PLS) using the SmartPLS 3.3.3 application. Based on the results of the study, it shows that system quality, information quality, and service quality have a positive effect on user satisfaction, and user satisfaction has a positive effect on net benefits.